Aging out of foster care: The experiences of former foster youth who successfully navigated this transition. (June 2021) - Hedenstrom, Margot
Foster youth face high risks and poor outcomes after aging out of care resulting in great economic and human costs to society. The purpose of the study was to describe life experiences of children aging out of the foster care system from the perspectives of adults who have successfully navigated this transition. Their life experiences during this period provided meaningful information for this study which helped to identify themes. Their perceptions of the periods during and after their transitions were explored to investigate supportive relationships, education, and workplace stability. Phenomenology was used to describe the experiences of nine young adults who had aged out of foster care. Participant ages ranged from 20 to 25 years old. Audiotaped semi-structured interviews were conducted for the study. Data analysis was ongoing throughout data collection. Four themes were identified: (1) "Facing a transition"; (2) "Depending on adults for help"; (3) "Making a difference for others"; and (4) "Moving forward with my life." These four themes highlighted the participants' experiences as they aged out of foster care. This study contributes to our understanding of the life experiences of former foster youth who are successful after the transition out of foster care. Recommendations for practice and research are identified.